2020
DOI: 10.1038/s41598-020-75229-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased intestinal permeability and gut dysbiosis in the R6/2 mouse model of Huntington’s disease

Abstract: Huntington’s disease (HD) is a progressive, multifaceted neurodegenerative disease associated with weight loss and gut problems. Under healthy conditions, tight junction (TJ) proteins maintain the intestinal barrier integrity preventing bacterial translocation from the intestinal lumen to the systemic circulation. Reduction of TJs expression in Parkinson’s disease patients has been linked with increased intestinal permeability—leaky gut syndrome. The intestine contains microbiota, most dominant phyla being Bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 47 publications
3
38
0
Order By: Relevance
“…Correspondingly, in a mouse model of HD (R6/1), an increase in Bacteriodetes (Gram−), but a decrease in Firmicutes (Gram+), which corresponds to the abovementioned study on HD patients, was noticed [147]. Very similar results were achieved independently in another mouse model of HD (R6/2) with the addition of proven increased intestinal permeability [148].…”
Section: Microbiomesupporting
confidence: 79%
“…Correspondingly, in a mouse model of HD (R6/1), an increase in Bacteriodetes (Gram−), but a decrease in Firmicutes (Gram+), which corresponds to the abovementioned study on HD patients, was noticed [147]. Very similar results were achieved independently in another mouse model of HD (R6/2) with the addition of proven increased intestinal permeability [148].…”
Section: Microbiomesupporting
confidence: 79%
“…Consistent with this notion, recent studies showed gut barrier dysfunction and increased gut permeability in mouse models of AD and dementia patients [ 66 , 67 , 68 ]. Moreover, the integrity of the epithelial gut barrier is reduced with aging and neurodegenerative conditions [ 69 , 70 , 71 ]. Consistent with these findings, our RT-qPCR and immunohistochemistry data showed a significantly reduced expression of tight and adheren junction proteins in the colon tissues of 5xFAD mice compared to their age-matched control littermates, suggesting compromised gut barrier function in AD condition.…”
Section: Discussionmentioning
confidence: 99%
“…Unintended weight loss is a hallmark of Huntington disease (HD), an autosomal dominant inherited neurodegenerative disorder caused by a CAG repeat expansion in the HTT gene, and occurs in both patients and premanifest mutation carriers, as well as many genetic animal models of the disease. 1,2 Recently, we found that body weight is a robust predictor of the rate of clinical progression in patients with HD. 3 Patients with a higher body mass index (BMI) at their first visit deteriorated more slowly in the motor, cognitive, and functional domains, independent of disease severity at baseline and mutant CAG repeat size.…”
mentioning
confidence: 99%